Trajetórias de vida de ex-alunas do “Colégio das Freiras”: o Colégio Nossa Senhora Auxiliadora (Sousa-PB, 1958-1985) - Estrela, Ana Paula (2023)
This dissertation aims to analyze the life trajectories and development of female Catholic education at Nossa Senhora Auxiliadora School located in Sousa-PB, during the period of 1958 to 1985, when education was exclusively for girls. This paper’s focus is on students in the Pedagogical Course. It is discussed the education of women, centered on teaching, aligned with Catholic faith ideals, and explored how discourses were based on life trajectories and gender identities through educational experiences at the above mentioned institution. Employing Oral History, where former students, teachers, and former principal were interviewed. In addition to oral reports, documentary sources include the school magazines and memoirs detailing the institution's history and educational philosophy. The research draws thought the Cultural History and History of Educational institutions theoretical framework, connecting with the categories of Catholic education, gender, and memory, engaging with authors such as Foucault (2014), Barros (2005), Louro (1997), Soares (2008), Scott (1995), Dominique Julia (2001), Portelli (2001), and Ferreira (2002). Women's identities were shaped by the school's philosophy, aiming to instill attitudes for confessional discipline. We examine life trajectories considering experiences and teachings at Nossa Senhora Auxiliadora School, analyzing these women's teaching professionalization, a prevalent reality during the studied time period. The research methodology involves discussing these women's memories and life experiences, focusing on constructing femininity through their education at the mentioned school.